The relationship among self-efficacy, teacher social support, and self-regulated learning of elementary school students - Aniva Kartika; Miftachul Jannah (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2024)
The goal of this study is to examine how self-efficacy and teacher social support relate to self-regulated learning in 4th and 5th-grade elementary school students. A quantitative correlation research method was employed, utilizing questionnaires to assess self-efficacy, teacher social support, and self-regulated learning. The research participants were 4th and 5th grade students in two elementary schools in Surabaya with a research sample of 156 people aged 9-12 years, comprising 91 girls and 65 boys. Data analysis was conducted using a multiple linear regression test utilizing IBM SPSS version 26. The result of this study showed that there is a relationship between self-efficacy and teacher's social support for self-regulated learning of elementary school students with a significant value (p=0.021). However, when analyzed individually, the self-efficacy variable did not significantly affect self-regulated learning (p = 0.596), whereas teacher social support did have a significant impact (p = 0.006). The coefficient of determination (R²) obtained was 0.079, indicating that self-efficacy and teacher social support together explain only 7.9% of the variance in self-regulated learning. This suggests that a substantial proportion of self-regulated learning in elementary school students is influenced by other factors